Arctic sea-ice drift vectors using a DM (daily-maps) approach. - Lavergne, Thomas (Norwegian Meteorological Institute, 2020)
Underlying dataset for the Lavergne et al. (2020) manuscript in EGU The Cryosphere Discussion. Processed from GCOM-W1 AMSR2 36.5 GHz (Ka-band) imagery. See the manuscript for more details.